Evaluasi dan Perbaikan Konten dan Navigasi Website Pendidikan Vokasi Universitas Brawijaya dengan Pendekatan Human-Centered Design (HCD) - Afif Imaduddin; Hanifah Muslimah Az-Zahra; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Vocational Education of Universitas Brawijaya has a website located at vokasi.ub.ac.id. which helps in providing information to its users. The results of interviews with users, there are many problems including web sites considered less informative, the content of the lecture schedule there is no name of the lecturer, there is no information or content about the prospects regarding their respective majors, and than that PK2MABA information that is less detailed and schedule guest lecture. Based on the problems, an evaluation of website content was using the Human-Centered Design (HCD) approach, it consisted of understanding and specifying the context of use are including stakeholders in this study, Vocational Education PSIK staff and users are consisted of active students, prospective students and alumni. Furthermore, it produces a specifying the user requirements to define content issues according to the needs of users and stakeholders. At this stage there are 20 content issues obtained from interviews with respondents, and producing design solution by conducting card sorting testing that produces sitemaps according to the highest score on the menu chosen by the respondent and tree testing at the initial test on the 20 contents there are 9 contents below the average score. Testing the prototype design using The Single Easy Questin (SEQ) questionnaire was given to 9 respondents with an assessment of 5.9 from an average score of 5.5.